Correlation of methylation of toll-like receptor 4 (TLR4) and interleukin-6 (IL6) promoter with insulin resistance in obese adolescents - Ratih Feraritra Danu Atmaja; Dian Caturini Sulistyonigrum; Emy Huriyati; Ahmad Hamim Sadewa; Rina Susilowati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Chronic inflammation can lead to insulin resistance in obesity. Increased mRNA expressionof inflammatory markers such as toll-like receptor 4 (TLR4) and interleukin 6 (IL6) werereported both in the tissue and the peripheral blood of obese adolescent and correlatedwith insulin resistance. DNA methylation surrounding TSS region is known to regulate thelevel of a gene expression. The aim of the study was to investigate the methylation statusof TLR4 and IL6 promoter in peripheral blood of obese adolescent and its correlation toinsulin resistance. This was a cross sectional study with observational analytic approached.Fifty adolescents with obesity from Yogyakarta Special Region, aged 15-18 years,z-score value >2 SD, no experience of any acute infections within 2 weeks and signed ininformed consent, were selected in this study. Subjects with diabetic mellitus, incompletedata and DNA concentration of <20 μg/mL were excluded. DNA samples were extractedfrom peripheral blood of the subjects. The bisulfite converted DNA was analyzed formethylation level with direct sequencing. Correlation analysis using Spearman test wasperformed with significance value was set at p<0.05. No methylation in TLR4 promoterwas detected in all subjects. The methylation level of IL6 was transformed to categoricalvariable. Four (8%) subjects with insulin resistance and 2 (4%) without insulin resistancehad methylation on a CpG site. Methylation of IL6 was not statisticaly different betweeninsulin resistance and non-resistance adolescent (p=0.635). The significant correlationwas not found between methylation level in IL6 promoter with insulin resistance (HOMAIR)(r=0.051). Cell specific of methylation mechanism, characteristic of subjects andtypes of samples were suspected causing those results. In conclusion, no correlationbetween methylation levels of TLR4 promoter and IL6 with insulin resistance in obeseadolescent was observed in this study.